1984
DOI: 10.1107/s0108270184009707
|View full text |Cite
|
Sign up to set email alerts
|

Structure of calcium chloride–sarcosine (1/3), CaCl2.3C3H7NO2, in the ferroelectric phase

Abstract: Abstract. Mr=378.3, orthorhombic, Pn2,a, a= 9. 122 (4), b = 17.408 (4), e= 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The crystal structure was reported by Ashida et al (1972) at ambient conditions in the centrosymmetric space group Pnma. Later, Mishima et al (1984) have found a phase transition to a non-centrosymmetric, ferroelectric phase at 127K. The ferroelectric structure has symmetry Pn2 1 a.…”
Section: Other Nonstandard Amino Acidsmentioning
confidence: 98%
“…The crystal structure was reported by Ashida et al (1972) at ambient conditions in the centrosymmetric space group Pnma. Later, Mishima et al (1984) have found a phase transition to a non-centrosymmetric, ferroelectric phase at 127K. The ferroelectric structure has symmetry Pn2 1 a.…”
Section: Other Nonstandard Amino Acidsmentioning
confidence: 98%
“…6). Examples of the first subtype are Sar 2 ÁMnCl 2 Á2H 2 O (Rzaczynska et al, 2002) (Silva et al, 2001) [an analogue of GlyÁNiCl 2 Á2H 2 O (Fleck & Bohatý, 2004) and GlyÁMnCl 2 Á2H 2 O (Clegg et al, 1987)] and Sar 3 ÁCaCl 2 (Mishima et al, 1984) (similar to Gly 3 ÁCeCl 3 ; Fleck, Held et al, 2008). It is noteworthy that the structures of SarÁMnCl 2 Á2H 2 O and GlyÁMnCl 2 Á2H 2 O are so closely related that even the unitcell parameters agree reasonably well (allowing for the additional CH 3 group of sarcosine), confirming that the crystal structures are not merely topologically similar.…”
Section: Figurementioning
confidence: 99%
“…Services for accessing these data are described at the back of the journal. Mishima et al (1984) and Ashida et al (1972) Symmetry codes: (i) x; Ày; z þ 1 2 ; (ii) x; y; z þ 1; (iii) Àx; y; Àz þ 3 2 ; (iv) Àx þ 1 2 , Ày þ 1 2 ; Àz þ 2; (v) Àx þ 1 2 ; Ày þ 1 2 ; Àz þ 1. Special details Experimental.…”
Section: Data Collectionmentioning
confidence: 99%
“…Sarcosine, also known as N-methylglycine (CH 3 NH 2 + CH2OO) − , is a natural amino acid inhibiting two hydrogen atoms which are located at the nitrogen atom. ere have been several reports investigating qualitatively the crystal structure of sarcosine in pure [9] and made on several crystalline complexes with organic and inorganic acids derivatives [10][11][12][13][14][15][16][17]. is amino acid is found naturally in star�sh, sea urchins and in the antibiotic actinomycin [18], and is also used in certain cosmetics [19].…”
Section: Introductionmentioning
confidence: 99%